National Development Council 31st Meeting Sept. 24 & 25 1976 Summary Record - Planning Commission (Planning Commission, 1976)
Welcoming the Chief Ministers and others to the meeting of the National Development Council, the Prime Minister, Smt. INDIRA GANDHI stated that since NDC’s last meeting which was held three years back the Nation had to face serious political and economic challenges. The fact that a meeting of the NDC had been convened to consider the final version of the Fifth Five Year Plan was indicative of the fact that the Nation had been able effectively to cope with these challenges.
Government of India Planning Commission
Government of India Planning Commission